STEM-ORIENTED TEACHING OF COMPUTER ARCHITECTURE IN DEVELOPING ENGINEERING THINKING OF FUTURE COMPUTER SCIENCE TEACHERS - Shamonia, Volodymyr; Soroka, Maksym; Semenikhina, Olena (Physical and Mathematical Education, 2025)
Formulation of the problem. The article substantiates the pedagogical feasibility of using the Proteus simulation environment in the process of STEM-oriented teaching of the "Computer Architecture" course with the aim of developing students' engineering thinking. The relevance of the study is determined by the need to train specialists capable of designing and analyzing digital devices, making technically sound decisions, and integrating knowledge from computer science, physics, mathematics, and electronics. Within the framework of the study, a pedagogical experiment was conducted with students who worked in different digital environments. Materials and methods. Research methods include: analysis of literature on STEM education, comparative analysis of the functionality of Proteus and Multisim environments, pedagogical experiment, and quantitative methods of analyzing the results. The experiment involved students of a pedagogical university studying hardware-oriented disciplines. Quantitative and qualitative analysis of the data made it possible to assess the level of content mastery, the dynamics of digital modeling skills development, the depth of reflection, and the manifestations of engineering thinking. Results. The results indicate that different simulation environments provide the acquisition of the basic content of the course; however, it is the Proteus environment that more actively stimulates technical creativity, flexibility in building models, and the ability to analyze and optimize circuits. Students working in Proteus demonstrated more diverse approaches to task completion, showed initiative in improving design solutions, and provided well-founded justifications for their choice of tools. Conclusions. The conclusion is made about the advisability of using Proteus in courses aimed at developing engineering thinking within the STEM paradigm. Methodological recommendations are offered for the optimal use of both environments depending on the didactic purpose. The obtained results have practical significance for the development of hardware-oriented academic courses, updating teaching methods, and implementing an interdisciplinary approach in the technical training of future computer science teachers.
Keywords: STEM education; engineering thinking; computer architecture; Proteus; digital modeling; technical creativity; training computer science teachers